Fault isolation in distributed generation connected distribution networks - Dewadasa, M.; Ghosh, Arindam; Ledwich, G.; Wishart, M. (The Institution of Engineering and Technology, 2011)
Protection of a distribution network in the presence of distributed generators (DGs) using overcurrent relays is a challenging task because of the changes in fault current levels and reverse power flow. Specifically, in the presence of current limited converter interfaced DGs, overcurrent relays may fail to isolate the faulted section either in grid connected or islanded mode of operation. In this study, a new inverse-type relay is presented to protect a distribution network, which may have several DG connections. The new relay characteristic is designed based on the measured admittance of the protected line. The relay is capable of detecting faults under changing fault current levels. The relay performance is evaluated using PSCAD simulation and laboratory experiments.